Unsupervised domain adaptation for LiDAR segmentation - Kong, Lingdong (Nanyang Technological University, 2022)
Transferring knowledge learned from the labeled source domain to the raw target domain for unsupervised domain adaptation (UDA) is essential to the scalable deployment of an autonomous driving system. State-of-the-art approaches in UDA often employ a key concept: utilize joint supervision signals from both the source domain (with ground-truth) and the target domain (with pseudo-labels) for self-training.